Update on Ankle and Foot Impingement - Armstrong, TM; Rowbotham, Emma; Robinson, Philip (Seminars in Musculoskeletal Radiology, 2023)
Ankle impingement syndromes are a well-recognized cause of chronic ankle symptoms in both the elite athletic and general population. They comprise several distinct clinical entities with associated radiologic findings. Originally described in the 1950s, advances in magnetic resonance imaging (MRI) and ultrasonography have allowed musculoskeletal (MSK) radiologists to further their understanding of these syndromes and the range of imaging-associated features. Many subtypes of ankle impingement syndromes have been described, and precise terminology is critical to carefully separate these conditions and thus guide treatment options. These are divided broadly into intra-articular and extra-articular types, as well as location around the ankle. Although MSK radiologists should be aware of these conditions, the diagnosis remains largely clinical, with plain film or MRI used to confirm the diagnosis or assess a surgical/treatment target. The ankle impingement syndromes are a heterogeneous group of conditions, and care must be taken not to overcall findings. The clinical context remains paramount. Treatment considerations are patient symptoms, examination, and imaging findings, in addition to the patient's desired level of physical activity.
Keywords: ankle impingement; ankle impingement syndromes; foot impingement